Facile preparation and photocatalytic hydrogen production of WS2 and its composites. (15th November 2022) - Liang, Kaiyue; Yin, Mingcai; Ma, Dehang; Fan, Yaoting; Li, Zhongjun
Abstract: Two-dimensional transition metal dichalcogenides, MoS2 and WS2 have been widely considered as promising materials for photocatalytic hydrogen production. However, compared with the widely investigated MoS2, researches on WS2 are much less. Besides, for the synthesis of WS2, methods suitable for large-scale preparation are still rare. Then in this paper, a facile method for the preparation of WS2 was developed based on the liquid-phase precipitation-calcination method reported previously. In specific, thiourea was introduced in the calcination process to realize the in-situ conversion of impurity WO3 to WS2 . As a result, WS2 was successfully prepared. More interestingly, a series of photocatalysts with different compositions and performances were easily obtained only through changing the thiourea amount. When no thiourea was used, a WS2 /WO3 heterostructure was constructed, while when excessive thiourea was introduced, an efficient WS2 /g-C3 N4 heterostructure (g-C3 N4 = graphitic carbon nitride) was fabricated. Moreover, their hydrogen production performances were investigated with Erythrosine B (ErB) and triethanolamine (TEOA) as photosensitizer and sacrificial agent, respectively. The results showed that the as-obtained WS2 has a comparable H2 -evolving activity (1686.3 μmol h −1 g −1 ) to the WS2 /WO3 (1637.8 μmol h −1 g −1 ), and the WS2 /g-C3 N4 owns the highest performance (2428.7 μmol h −1 g −1 ). This work provides a facile and feasible route for the preparation of efficient WS2 -based photocatalysts. Highlights: WS2 was easily prepared by liquid pahse-calcination method via thiourea introduction. WS2 /WO3 and WS2 /g-C3 N4 were also obtained only through changing thiourea amount. Efficient photocatalytic hydrogen production on WS2 was achieved by dye-sensitization.